SEDIMEN LAUT SEBAGAI PROXY DALAM MENENTUKAN DINAMIKA IKLIM DI MASA LAMPAU - Septriono Hari Nugroho (Pusat Penelitian Oseanografi LIPI, 2018)
MARINE SEDIMENT AS PROXY TO DETERMINE CLIMATE DYNAMICS IN THE PAST. Studying the dynamics of climate change in the past is important and necessary, because it can serve as a basis for understanding the modern climate and the causes of its variations and changes. Evidence of past climatic conditions is usually archived on traces in nature that provide a proxy of past climatic conditions that we can explore. One of the major sources of proxy data for paleoclimate reconstruction is marine sediment. Microfossils usually used for quantitative proxy is foraminifer, diatom, pollen and etc. For the purposes of paleoclimate, the most important material is foraminifera. The paleoclimate results from the remains of carbonate and silica organisms have been generated from four types of analyzes: (a) oxygen isotope composition, especially calcium carbonate in foraminifer test (b) quantitative interpretation of species and its spatial variation through (c) the ratio of Mg / Ca to the foram test, which is related to temperature, and (d) the morphological variation in certain species resulting from environmental factors.